LATIHAN SOAL POSSESSIVPRONOMEN SISWA JERMAN SISWA KELAS XI SMA NEGERI 1 TAMAN DARI LKS MEINE FAMILIE - MAHARANI, AISYAH (LATERNE, 2016)
German is the subject to develop oral and written skills. to understand and express information, thoughts, feelings, and developing science and culture. Therefore, it needs the capable of implementing a standard of competence and basic competencies in the curriculum German Language. One of them is by the book. LKS (Student Worksheet) is a book that contains knowledge derived from the basic competencies set out in the curriculum, where it is used by students to learn. But unfortunately not all of Student Worksheet can be applied in all schools, considering the applying curriculum  in every school is different.   Formulation of the problem in this research is how the results or the outcome of learning german in class XI student of SMAN 1 Taman by using worksheets Meine Familie compiled by Vani Valeriani mukin in 2016. This study aimed to describe the results studied German class XI student of SMAN 1 Garden with using Student Worksheet Meine Familie compiled by Vani Valeriani mukin in 2016.   This study is a qualitative research with descriptive approach. In practice there are three stages of the procedure performed, namely: planning, implementation on the ground, and data processing. The data used are student learning outcomes. Data obtained using a test instrument that is done twice (before and after using LKS Meine Familie) and supported by data from student questionnaires.   Results showed that changes in the number of average value towards a better grade from the initial tests with the average value of 70.6667 classes (not yet reached the standart, ie 75) increases in final test with an average value of 82 , 1333 (has reached the standard of note that student must get). Then the student questionnaire results show the results with the criteria of